2001
DOI: 10.1037/1076-8971.7.3.622
|View full text |Cite
|
Sign up to set email alerts
|

Jury decision making: 45 years of empirical research on deliberating groups.

Abstract: This article provides a comprehensive review of the empirical research on jury decision making published between 1955 and 1999. In total, 206 distinguishable studies involving deliberating juries (actual or mock) were located and grouped into 4 categories on the basis of their focal variables: (a) procedural characteristics, (b) participant characteristics, (c) case characteristics, and (d) deliberation characteristics. Numerous factors were found to have consistent effects on jury decisions: definitions of ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
339
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(349 citation statements)
references
References 215 publications
(666 reference statements)
7
339
1
2
Order By: Relevance
“…This is true when it is clear to most everyone what the "right" thing to do is, such as when two-thirds of jurors believe that a defendant is innocent prior to deliberations, and the jury predictably delivers a not-guilty verdict (Devine et al 2001). It is also true when strong vested interests are in play and a powerful individual or coalition can override, or buy off, all resistance to whatever decision it favors (Bueno de Mesquita 2009).…”
Section: Resultsmentioning
confidence: 99%
“…This is true when it is clear to most everyone what the "right" thing to do is, such as when two-thirds of jurors believe that a defendant is innocent prior to deliberations, and the jury predictably delivers a not-guilty verdict (Devine et al 2001). It is also true when strong vested interests are in play and a powerful individual or coalition can override, or buy off, all resistance to whatever decision it favors (Bueno de Mesquita 2009).…”
Section: Resultsmentioning
confidence: 99%
“…It is also, however, possible that these decisions could guide individuals toward unhelpful or even destructive outcomes. Even far-reaching constructs such as racism, poor numeric reasoning, jury bias, flawed physician decision making, and negative economic outcomes have been linked to decision making biases [3][4][5][6][7].…”
Section: Availability Heuristicmentioning
confidence: 99%
“…By only using mock jurors, the ecological validity and supposedly the external validity of the study is weakened. Consequently, Devine et al (2001) have reported that the use of mock jurors have been criticized by many judges for lacking realism. At the same time, no other approach is capable of controlling influential extraneous variables that are related to the case as effectively as is possible with the use of mock jurors.…”
Section: Discussionmentioning
confidence: 99%
“…Hundreds of thousands of U.S. citizens serve on juries every year, and a significant proportion of the U.S. population will serve on juries at some time in their lives (Devine, Clayton, Dunford, Seying, & Pryce, 2001). Additionally, several countries use a similar system as the U.S. in which the jury is made up entirely of laypersons (e.g., Australia, Canada, UK, New Zealand, Russia, and Spain).…”
Section: Jury Decision Makingmentioning
confidence: 99%